The Juridical Study of the Role of BPN in Eradicating the Land Mafia - Simamora, Rahmat Hidayat (TABELLIUS: Journal of Law, 2023)
The land mafia is a serious problem that can harm society and the country. As a serious problem, law which is a state instrument in managing national land affairs mandated to be able to eradicate the land mafia, has not been optimally implemented. This is proven by the increasing number of land mafia cases, including in the Medan City area. This writing uses sociological or empirical legal research. Based on the studies conducted, it is known that the implementation of the BPN's role in efforts to eradicate the land mafia in Medan City is currently not optimal, this is because the BPN acted after there were public complaints regarding land mafia cases in the community. The juridical obstacle is the absence of regulation regarding criminal law enforcement processes in the Technical Instructions of the Ministry of Agrarian Affairs and Land Affairs Number 01/JUKNIS/D.VII/2018 concerning Prevention and Eradication of Land Mafia. The next obstacle is the obstacle in the aspect of law enforcement which consists of internal and external obstacles. Internal constraints are constraints from the BPN institution. External constraints are obstacles related to the legal culture in society related to eradicating the land mafia.Keywords: Agrarian; Land; Mafia.